Smart Security System Using Chatbot - S. Vinothini; A. R. Gokul; S. Gowtham; E. Manoj; S. Sowndharya; T. Subhapradha; M. Jothilakshmi (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Security is the main issue that must be addressed in the present society. In terms of house security we represent a system that uses the internet networking to give an easy path to our stoner to control the different appliances at home. Now a days the technology is adding fleetly, that leads to an upgradation in home security system. Home security is a veritably useful operation of IoT and we're using it to produce an affordable security system for homes. The home security system using ESP- 32 CAM and Telegram operation is a design that aims to enhance the security of homes and other private demesne. The system consists of an ESP- 32 CAM module, which captures live videotape footage and sends it to a Telegram bot. The bot also sends announcements to the proprietor's Telegram account when stir is detected. The design is enforced using the Arduino IDE and colorful libraries, including the Telegram Bot Library and ESP32 CAM library. The system is designed to be low- cost, easy to install and use, and largely effective at precluding burglary and other security breaches. The design provides an innovative result for enhancing home security using ultramodern technologies and communication channels.
Keywords: Home Security; Internet of effects; CAM; Telegram operation